2019
DOI: 10.21608/ejnf.2019.79390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humic Acid and Selenium Supplementation on Immunity and Performance of Newborn Calves

Abstract: orty newly born male Holstein calves were distributed randomly into four treatments (n=10) to receive no additive (control), Se (2.3mg/head/d), Humic acid (HA, 15 g/head/d), HA + Se (15 g HA+2.3 mg Se/head/d) to evaluate the effect of treatments on calves performance, serum IgG concentration and some blood parameters. Calves received their respective treatments for four consecutive days after birth as treatments were mixed with colostrum and blood samples were taken at 12, 24, 48 and 72 hrs. after birth and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…The decrease in glucose in the Vit. E and Se group agreed with that reported by Ebrahimi et al (2009), and disagreed with that reported by Mudgal et al (2012), andKanana et al (2019). This hypoglycemia may be due to the impaired gluconeogenic capability of cells in the animal liver (Sharma et al, 2005).…”
Section: Effects Of Addition Of Vit E Se and Spirulina Platensis On H...mentioning
confidence: 51%
“…The decrease in glucose in the Vit. E and Se group agreed with that reported by Ebrahimi et al (2009), and disagreed with that reported by Mudgal et al (2012), andKanana et al (2019). This hypoglycemia may be due to the impaired gluconeogenic capability of cells in the animal liver (Sharma et al, 2005).…”
Section: Effects Of Addition Of Vit E Se and Spirulina Platensis On H...mentioning
confidence: 51%